Litter Production and Decomposition Rate in the Reclaimed Mined Land under Albizia and Sesbania Stands and Their Effects on some Soil Chemical Properties - Ali Munawar; . Indarmawan; Hery Suhartoyo (UNIVERSITY OF LAMPUNG, 2011)
Vegetation establishment is considered as a critical step of mined land rehabilitation. The growing plants do not only prevent soil erosion, but also play important roles in soil ecosystem development. Their litterfall is the main process of transferring organic matter and nutrients from aboveground tree biomass to soil. Thus, its quantification would aid in understanding biomass and nutrient dynamics of the ecosystem. This study was aimed to investigate the litter production and its decomposition rate in a reclaimed mined land using albizia and sesbania, and theireffects on some soil properties. The litter under each stand was biweekly collected for four months. At the same time litter samples were decomposed in mesh nylon bags in soils and the remaining litters were biweekly measured. Soil samples were taken from 0-15 cm depths from each stand for analyses of soil organic C, total N, and cation exchange capacity (CEC). The results demonstrated that total litter production under albizia (10.58 t ha-1 yr-1) was almost twice as much as that under sesbania stands (5.43 t ha-1 yr-1). Albizia litter was dominated by leaf litter (49.26%) and least as understory vegetation (23.31%), whereas sesbania litter was more evenly distributed among litter types. Decomposition rates of all litters were fastest in the initial stage and then gradually decreased. Sesbania leaf litters decomposed fastest, while albizia twigs slowest. Differences in the litter production and decomposition rates of the two species had not sufficiently caused significant effects on organic-C, total N, and CEC of the soilsafter one year of revegetation.Keywords: Albizia (Paraserianthes falcataria), decomposition rates, litter, mined land, Sesbania grandiflora